Analisis Pembiayaan Sektor Jasa Dunia Usaha Pada Perbankan Syariah di Indonesia - Yuningsih, Ayu; Afandi, Akhsyim (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
Financing is one of the main functions of Islamic banking. In its operational activities, Islamic banking channel most of its assets into financing. However, the financing trend in this sector always fluctuates from year to year and tends to decline. This study aims to analyze the factors that influence the financing of the business services sector in Islamic banking in Indonesia. This study uses time-series data which is the monthly data of the aggregate financial statements of Sharia Commercial Banks and Sharia Business Units in Indonesia. The analysis method used in this study is Autoregressive Distributed Lag (ARDL). The results showed that the variables that influence the financing of the business services sector in the short term are third party funds (DPK), equivalent rate of financing (ERP) and Industrial Production Index (IPI). Whereas in the long run, the variables that influence the financing of the business services sector are third party funds (DPK), return on assets (ROA), non-performance financing (NPF), Industrial Production Index (IPI). While the variable interest rates and exchange rates both in the short and long term do not affect the financing of the business services sector.